2019
DOI: 10.1111/aogs.13526
|View full text |Cite
|
Sign up to set email alerts
|

Preventability review of severe maternal morbidity

Abstract: Introduction:Severe maternal morbidity (SMM) is rising globally. Assessing SMM is an important quality measure. This study aimed to examine SMM in a national cohort in New Zealand. Material and methods:This is a national retrospective review of pregnant or postpartum women admitted to an Intensive Care Unit or High Dependency Unit during pregnancy or recent postpartum. Outcomes were rates of SMM and assessment of potential preventability. Preventability was defined as any action on the part of the provider, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…In reviewing the 31 cases of near miss, ten were viewed to have some aspect of provider/system related factor contributing the severe morbidity. This is in keeping with previous studies utilising Geller's preventability model which have shown that about one-third of cases have some level of provider or system related preventability 7,13,14 . Most cases of provider related preventability relate to lack of diagnosis/recognition of decompensation, followed by the lack of ability to undertake the appropriate procedures in a timely fashion.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In reviewing the 31 cases of near miss, ten were viewed to have some aspect of provider/system related factor contributing the severe morbidity. This is in keeping with previous studies utilising Geller's preventability model which have shown that about one-third of cases have some level of provider or system related preventability 7,13,14 . Most cases of provider related preventability relate to lack of diagnosis/recognition of decompensation, followed by the lack of ability to undertake the appropriate procedures in a timely fashion.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, our preventability review was an internal review subject to bias -external review using trained multidisciplinary cohort of staff may provide a more objective assessment of preventabilitythis has been successfully undertaken in various local and national settings in New Zealand (NZ) but requires further validation in the Australian setting 7,13,14 Conclusion This is the first study to characterise obstetric ICU patients in a regional Australian setting and overall maternal morbidity and obstetric ICU admission rates are reassuringly low. Obstetric haemorrhage and hypertensive disorders of pregnancy are the most common diagnoses for admission, although many cases are admitted for more intensive monitoring rather than for specific interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review in New Zealand showed that at least onethird of SMM cases may be preventable, 29 and other studies have observed a high proportion of SMM due to obstetric haemorrhage. 13,17,30,31 It follows that the alleviation of anaemia in early-or mid-pregnancy might reduce both transfusion and SMMespecially those SMM elements more plausibly linked to a low haemoglobin ( Figure S1).…”
Section: Discussionmentioning
confidence: 98%
“…This is a national retrospective cohort study of SMM cases in A SMM case was defined as any woman admitted to an Intensive Care Unit (ICU) or High Dependency Unit (HDU) during pregnancy, up to six weeks postpartum. 6 ICU admission has 79-86% sensitivity and 88-95% specificity for a SMM event and identifies about 30% of SMM cases and usually the most severe. [11][12][13] Adverse fetal/ neonatal outcomes were defined as one or more of the following: death (miscarriage, abortion, fetal death, or neonatal death), hypoxic ischaemic encephalopathy (HIE), Apgar score less than seven at five minutes, and/or, admission to a Neonatal Intensive Care Unit (NICU) or SCBU.…”
Section: Methodsmentioning
confidence: 99%